Milieu effects on the Dark Triad traits and their sex differences in 49 countries. (October 2022) - Jonason, Peter K.; Czerwiński, Stanisław K.; Tobaldo, Francesca; Ramos-Diaz, Jano; Adamovic, Mladen; Adams, Byron G.; Ardi, Rahkman; Bălțătescu, Sergiu; Cha, Yeow Siah; Chobthamkit, Phatthanakit; El-Astal, Sofián; Gundolf, Katherine; et al.
Abstract: Most research on the development of personality traits like the Dark Triad (i.e., narcissism, Machiavellianism, and psychopathy) focuses on local effects like parenting style or attachment, but people live in a larger society that may set the stage for any local effects. Here we paired nation-level data on the traits from 49 nations with several milieu indicators (e.g., life expectancy, homicide rates) from three timepoints (and change among them) where the average participant (≈ 22yo) would have been a child (≈ 6yo), a pre-teen (≈ 11yo), and a teenager (≈ 16yo). Congruent with previous research, variance in narcissism was far more sensitive to variance in milieu conditions in general and across all three time points than variance in Machiavellianism or psychopathy. The milieu conditions differentiated the traits somewhat with income and education revealing negative correlations with narcissism, positive correlations with Machiavellianism, and null correlations with psychopathy. Sex differences in Machiavellianism and narcissism were correlated with homicide rates across the three timepoints. The evidence that changes in milieu conditions in ones' past predicts the traits was erratic, but larger sex differences in the traits were associated with decreased life expectancies and homicide rates between childhood and pre-teens. Highlights: Conducted a secondary analysis on details about the Dark Triad traits Paired the traits with country-level indicators from three past time points Adult narcissism/psychopathy linked to stable and harsh conditions in one's past. Childhood modernity/stability linked to adult Machiavellianism. Sex differences in the traits grew with unemployment and homicide rates.